2016
DOI: 10.1159/000443663
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Staphylococcus aureus</i></b> Induces Shedding of IL-1RII in Monocytes and Neutrophils

Abstract: Interleukin 1 (IL-1) β is a critical cytokine that orchestrates host defenses against Staphylococcus aureus and is crucial for the eradication of bacteria. The production and action of IL-1β are regulated by multiple control pathways. Among them, IL-1RII (the type II IL-1 receptor) acts as a decoy receptor and has been shown to regulate the biological effects of IL-1β. High levels of soluble IL-1RII are present in septic patients; however, the stimuli that regulate the expression and release of IL-1RII in path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…During the infection process of invasive S. aureus , pathogen-associated-molecules initiate the innate immune system leading to activation and recruitment of neutrophils and macrophages and the production of pro-inflammatory cytokines, most notably TNF-α, IL-1β, and IL-6 (Bekeredjian-Ding et al, 2015; Giai et al, 2016; Zhao et al, 2016). It was reported that the secretion of inflammatory cytokines IL-6 increased with increasing concentrations of S. aureus (Chen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…During the infection process of invasive S. aureus , pathogen-associated-molecules initiate the innate immune system leading to activation and recruitment of neutrophils and macrophages and the production of pro-inflammatory cytokines, most notably TNF-α, IL-1β, and IL-6 (Bekeredjian-Ding et al, 2015; Giai et al, 2016; Zhao et al, 2016). It was reported that the secretion of inflammatory cytokines IL-6 increased with increasing concentrations of S. aureus (Chen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that Staphylococcus aureus induces IL‐1R2 shedding by myeloid cells and that in monocytes the release of IL‐1R2 was highly dependent on the expression of protein A, a complex virulence factor, contributing to evasion of immune clearance. S. aureus protein A rapidly activated ADAM17 in airway epithelial cells and macrophages, leading to IL‐1R2 shedding and consequently reducing IL‐1β availability, therefore negatively modulating the subsequent inflammatory response critical for bacterial eradication during early systemic infection and contributing to the bacterial persistence in blood . Thus, IL‐1R2 shedding by S. aureus would represent a novel mechanism of immune evasion by this microorganism.…”
Section: The Decoy Receptor Il‐1r2mentioning
confidence: 99%
“…S. aureus protein A rapidly activated ADAM17 in airway epithelial cells and macrophages, leading to IL-1R2 shedding and consequently reducing IL-1β availability, therefore negatively modulating the subsequent inflammatory response critical for bacterial eradication during early systemic infection and contributing to the bacterial persistence in blood. 61 Thus, IL-1R2 shedding by S. aureus would represent a novel mechanism of immune evasion by this microorganism.…”
Section: Il-1r2 Expressionmentioning
confidence: 99%
“…It is, by some measures, the most important type of immunity we have.” has lost none of its actuality. From the beginning, the journal has been covering research in the area of innate immunity in a broad sense, for example invertebrate immunity [4-6], innate recognition [7-9], the cell biology of innate immune cells [10-12], and complex human diseases [13-15]. …”
mentioning
confidence: 99%